Phylogenetic taxonomy of Leishmania (Viannia) braziliensis based on isoenzymatic study of 137 isolates (1997)
Biochemical characterization of 137 Leishmania braziliensis isolates from South and Central America, and from selected endemic foci in Bolivia, Brazil and Colombia, performed by isoenzymatic electrophoresis using 10 enzymatic systems, showed a high enzymatic polymorphism (44 zymodemes obtained) based on the variation of a small number of enzymes. Cladistic analysis showed close links between the zymodemes within the L. braziliensis s.s. cluster. The position of 2 Colombian zymodemes obtained (MON*204 and MON*205) justify the inclusion of L. peruviana within the L. braziliensis cluster.